The Rise of the Anthroposphere since 50,000 Years: An Ecological Replacement of Megaherbivores by Humans in Terrestrial Ecosystems? - Bocherens, Hervé (Frontiers in Ecology and Evolution, 2018)
Megaherbivores fulfilled a number of important ecological function in terrestrial ecosystems and behaved as ecological engineers since 300 million years until around 12,000 years ago. The late Pleistocene extinction led to the loss of important ecological functions that were partially restore by agriculturists humans through an ecological replacement. Understanding better the differences and similarities in the ecological impact of megaherbivores and agricultural humans should help to predict the future of terrestrial ecosystems.